Pendekatan Simulasi untuk Analisis Antrian pada Bengkel Servis PT. X - Prima Denny Sentia; Ilyas Ilyas; Riyan Haikal (Jurnal Optimasi Sistem Industri, 2016)
PT. X is an authorized dealer and service provider of a reputable car product that provides sales and maintenance services. Total number of counters and stalls owned by PT. X cannot be considered optimal based on the number of cars that will be serviced. Long queues cause customers postponinge the maintenance service and reschedule them to another day. The purpose of this study is to analyze the queue characteristic of the simulation results in the service counters and to design improvement of the scenarios. The study was conducted to implement a simulation model on a service system in order to determine an optimal number of service stations which is appropriate with the waiting time that has been targeted by the company. The analysis of the scenario carried out refers to the target that needs to be achieved by the company that is 15 minutes waiting time to call by counter and 120 minutes waiting time to service. Based on the possibilities occurred, there are 11 proposed improvement scenarios that can be applied in the company. The results from the analysis stated that scenario No. 8 that add two counters and two maintanance stalls in the service station has average waiting time which closed with targeted time set by the company. Therefore, scenario No. 8 is chosen as a proposed improvement actiion. By implementing this scenario it is expected that average waiting time to call by a counter is only on 16,845 minutes on Thursday and the average waiting time to service is only 124,63 minutes on Wednesday.